Clinical and biometric evaluation of root coverage by CPF following FGG method using citric acid - AA. Khoshkhonejad; M. Mohseni Salehi Monfard (Tehran University of Medical Sciences, 1993)
Two Root coverage methods of free gingival graft method (FGG) and coronally positioned flap (CPF) by using citric acid were evaluated in anterior mandibular labial site of 16 patients. The measurements were done before first FGG surgery, after FGG and two months following the second surgery. The results showed 1% improvement of root coverage after surgery while in two stage CPF method by using citric acid, significant effect of citric acid was obtained. The width of Keratinized gingiva changed to 6.25mm from 1.18mm which was statistically significant.